2020
DOI: 10.1136/ijgc-2020-001646
|View full text |Cite
|
Sign up to set email alerts
|

Trends and survival outcomes of robotic, laparoscopic, and open surgery for stage II uterine cancer

Abstract: IntroductionA recent randomized clinical trial showed that minimally invasive surgery led to poorer survival compared with open surgery in early stage cervical cancer. We determined the trends in adoption of minimally invasive surgery and 5-year overall survival outcomes after open, laparoscopic-assisted, and robotic-assisted hysterectomy for stage II uterine cancer with cervical stromal involvement.MethodsData for patients with stage II uterine cancer were acquired from the National Cancer Database from 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…( 25 ) reported in an international European cohort observational study that early-stage cervical cancer patients undergoing MIS increased the risk of recurrence and death compared with those undergoing ARH. In addition, we observed that in many retrospective studies ( 28 , 30 , 33 , 41 , 47 , 51 , 57 , 59 ), the MIS group had a shorter follow-up time than that of the ARH group. In order to objectively evaluate the effect of MIS and ARH on the prognosis of patients with early-stage cervical cancer, more adequate follow-up time is needed.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…( 25 ) reported in an international European cohort observational study that early-stage cervical cancer patients undergoing MIS increased the risk of recurrence and death compared with those undergoing ARH. In addition, we observed that in many retrospective studies ( 28 , 30 , 33 , 41 , 47 , 51 , 57 , 59 ), the MIS group had a shorter follow-up time than that of the ARH group. In order to objectively evaluate the effect of MIS and ARH on the prognosis of patients with early-stage cervical cancer, more adequate follow-up time is needed.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, Abel et al. ( 33 ) revealed that stage II cervical cancer undergoing MIS or ARH revealed comparable 5-year survival rates. Nonetheless, some recent studies have demonstrated that early-stage patients undergoing MIS had poorer DFS and OS than those undergoing ARH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[131][132][133][134][135] Prospective cohort and retrospective studies suggest that robotic approaches perform similarly to laparoscopy and result in comparable or improved perioperative outcomes. [135][136][137][138][139][140] Oncologic outcomes appear to be comparable to other surgical approaches, although longer-term outcomes (including quality of life) are still being investigated. [141][142][143] In heavier patients, robotic surgery may result in less frequent conversion to laparotomy when compared with laparoscopic approaches and also appears to be safe and feasible in patients at higher anesthesiologic risk.…”
Section: Minimally Invasive Proceduresmentioning
confidence: 99%
“…It is also considered more ergonomic for the surgeon, as well as a more precise and, therefore, safer procedure than traditional laparoscopy. [1][2][3] At the Central Hospital Karlstad (Sweden), we perform around 100 robotic-assisted hysterectomies per year, of which the largest group, around 40, is because of uterine malignancy. Indications for the rest of the procedures are persisting premalignant conditions in the cervix, heredity of gynecological-or breast malignancy, benign fibroids in the uterus or excessive bleeding.…”
mentioning
confidence: 99%